Micro-credit institution’s services and sustainability of micro, small and medium-scale enterprises during Covid-19 pandemic in Kigezi region south western Uganda - Moses, Agaba; Siraje, Kaaya; Nafiu, Lukman Abiodun (Kabale University Interdisciplinary Research Journal (KURJ), 2022)
The study examined the effect of Microcredit institutions’ services on the sustainability of micro, small and medium size enterprises during the Covid-19 pandemic of the Kigezi region, South Western Uganda. The specific objectives were to: determine the effect of loan provision by microcredit institutions on the sustainability of MSMEs; determine the effect of the provision of the saving account by microcredit institutions sustainability of MSMEs, The study was conducted in the Kigezi region of Uganda. The region has six (6) districts namely: Kabale, Kisoro, Kanungu, Rukungiri, Rubanda and Rukiga. The Kigezi region is situated in Southwestern Uganda. The sample size was computed using Yamane’s sampling formulae and was based on a 5% level of precision. The research used both descriptive and cross-sectional surveys to gather information from various MSMEs records and panel procedures as well as a supplementary interview as methods of data collection. A cluster sampling procedure was applied to select the enterprises’ respondents. Enterprises’ owners and managers were the units of inquiry due to their importance as custodians of information on all the activities taking place in their respective MSMEs. The research population was divided into clusters (areas or districts) and the required sample was selected using simple random sampling. The study used an interviewer-administered structured questionnaire to collect the data. This suggests that increases in Loan Provision and Saving Accounts help to increase Sustainability. Results further indicate that of the aspects of Sustainability of MSMEs, Loan Provision has no significant effect ( =0.048, Sig=0.279); Saving Account has a significant effect ( =0.125, Sig=0.001); and Training on Managerial Skills has a significant effect ( =0.309, Sig=0.000). The study concludes that loan provision by microcredit institutions did not sustain MSMEs during the Covid-19 pandemic in Kigezi Sub-Region Uganda, accessing an adequate amount of credit is an important factor in increasing the development and growth of SMEs and increasing Saving accounts will increase Micro-credit Institutions Serviceability of MSMEs. The researchers recommend the use of sensitization of the clients and the use of other marketing tools.